Editorial: Economic and Statistical Studies - Society, Culture and Politics - El Director (2007)
The effort to keep the IECOS Journal at the service of research has materialized in issues 1 and 2, published in 2005 (April) and 2006 (September), respectively; now we intend to redouble our efforts to achieve a quarterly periodicity. We wanted the appearance of this issue to coincide with the inauguration of the new academic year 2007, as a good omen regarding the integration between teaching and research. It is our wish that research becomes an essential task for a significant number of teachers and students, which requires generating institutional consensus within our faculty that will allow us to allocate more resources to research.